What matters in households' inflation expectations? - Philippe Andrade; Erwan Gautier; Eric Mengus (Federal Reserve Bank of Boston, 2020)
We provide evidence that households discretize their inflation expectations so that what matters for durable consumption decisions is the broad inflation regime they expect. Using survey data, we document that a large share of the adjustment in the average inflation expectation comes from the change in the share of households expecting stable prices; these households also consume relatively less than the ones expecting positive inflation. In contrast, variations of expectations across households expecting a positive inflation rate are associated with much smaller differences in individual durable consumption choices. We illustrate how this mitigates the expectation channel of monetary policy.
Keywords: D12; D84; E21; E31; E52; 330; inflation expectations; Euler equation; survey data; imperfect information; adjustment costs; stabilization policies